Characteristic phytocenosis with Echinops albicaulis in the area of the pass Malaysary. (Experimental biology, 2016)
This article presents the results of studies on the floristic composition of plant communities with Echinops albicaulis Kar. & Kir. in the area of the pass Malaysary. The floristic composition of the community was represented Echinops 25-30 species of vascular plants. The most characteristic of these associations with the participation of Echinops albicaulis: calligonum-different-herb-grass, сalligonum- different-herb-grass-echinops, аrtemisia - echinops and аrtemisia. The floristic composition of plant communities with Echinops albicaulis characterized by agricultural significance. In economic value allocated 10 types of medicines, 14 kinds of food, 3 kinds of food, 4 kinds of technical, 9 species of ornamental, 3 kinds of honey, 6 and 4 species of poisonous species of rare endangered plants. Аgricultural significance allocated 10 types of medicines, 14 kinds of food, 3 kinds of food, 4 kinds of technical, 9 species of ornamental, 3 kinds of honey, 6 and 4 species of poisonous species of rare endangered plants. The floristic composition of Echinops community was presented 25-30 species of vascular plants.
Keywords: phytocenosis; floristic composition; Echinops albicaulis Kar. & Kir.